Selenomethionyl proteins produced for analysis by multiwavelength anomalous diffraction (MAD): a vehicle for direct determination of three-dimensional structure. - Hendrickson, W A (1990)
An expression system has been established for the incorporation of selenomethionine into recombinant proteins produced from plasmids in Escherichia coli. Replacement of methionine by selenomethionine is demonstrated at the level of 100% for both T4 and E. coli thioredoxins. The natural recombinant proteins and the selenomethionyl variants of both thioredoxins crystallize isomorphously. Anomalous scattering factors were deduced from synchrotron X-ray absorption measurements of crystals of the selenomethionyl proteins. Taken with reference to experience in the structural analysis of selenobiotinyl streptavidin by the method of multiwavelength anomalous diffraction (MAD), these data indicate that recombinant selenomethionyl proteins analyzed by MAD phasing offer a rather general means for the elucidation of atomic structures.